Adversaries at the Bedside: Advance Care Plans and Future Welfare - Kestigian, Aidan (Bioethics, 2016)
Advance care planning refers to the process of determining how one wants to be cared for in the event that one is no longer competent to make one's own medical decisions. Some have argued that advance care plans often fail to be normatively binding on caretakers because those plans do not reflect the interests of patients once they enter an incompetent state. In this article, we argue that when the core medical ethical principles of respect for patient autonomy, honest and adequate disclosure of information, institutional transparency, and concern for patient welfare are upheld, a policy that would allow for the disregard of advance care plans is self-defeating. This is because when the four principles are upheld, a patient's willingness to undergo treatment depends critically on the willingness of her caretakers to honor the wishes she has outlined in her advance care plan. A patient who fears that her caretakers will not honor her wishes may choose to avoid medical care so as to limit the influence of her caretakers in the future, which may lead to worse medical outcomes than if she had undergone care. In order to avoid worse medical outcomes and uphold the four core principles, caregivers who are concerned about the future welfare of their patients should focus on improving advance care planning and commit to honoring their patients’ advance care plans.